2016
DOI: 10.1016/j.jchf.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Variable Contribution of Heart Failure to Quality of Life in Ambulatory Heart Failure With Reduced, Better, or Preserved Ejection Fraction

Abstract: Fewer than one-half of patients with ambulatory HF rated HF as the greatest limitation to their QOL, suggesting that this important outcome will be difficult to affect by HF-targeted therapies alone, particularly in those with higher LVEFs and comorbidities. Patients with HF with better LVEF represent a distinct subtype with better overall QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Several available publications have defined the subset of patients with HFpEF who previously had HFrEF as heart failure with recovered ejection fraction 2,3,17 or heart failure with better ejection fraction 4,23 and have been using different EF cut-off points for defining this HF category (≥40%, 2 ≥45%, 17 and ≥50%…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several available publications have defined the subset of patients with HFpEF who previously had HFrEF as heart failure with recovered ejection fraction 2,3,17 or heart failure with better ejection fraction 4,23 and have been using different EF cut-off points for defining this HF category (≥40%, 2 ≥45%, 17 and ≥50%…”
Section: Discussionmentioning
confidence: 99%
“…These patients were clinically distinct from those with HFpEF and more similar to the HFrEF population from which they initially arose. Further studies found that HFiEF is associated with a better biomarker profile, quality of life, and event-free survival than continued HFrEF and HFpEF 3,4 but still experience a significant number of HF hospitalizations, suggesting persistent HF risk. 3 In this post hoc analysis of the Valsartan Heart Failure Trial (Val-HeFT) 5 database, we characterized the subjects who had improved their EF during the first 12 months of follow-up, evaluated the independent correlates of EF improvement, and determined whether their all-cause mortality was substantially different from the subjects whose EF remained reduced.…”
Section: See Editorial By Basuray and Fang See Clinical Perspectivementioning
confidence: 96%
See 1 more Smart Citation
“…The literature shows a lack of correlation between QOL and LVEF 12, 35, 36, 37, 38. However, Joyce et al 39 compared patients with reduced, preserved, and better LVEF (improvement in LVEF, ≥50%) and found that fewer than one-half of patients with ambulatory HF rated HF as the greatest limitation to their QOL. This suggested that it may be difficult to improve QOL using HF-targeted therapies alone, particularly in patients with higher LVEF and comorbidities 39 …”
Section: Discussionmentioning
confidence: 99%
“…Depending on the details of the populations studied, QOL impairment has been shown to be similar or slightly different between HFrEF and HFpEF groups. 19,27 This may reflect the characteristic pathophysiology of each of these LVEF HF subtypes, [28][29][30][31][32][33][34][35] and the fact that HFpEF in general encompasses older patients in whom age and accumulating comorbidities play an increasing role in limitation. 36 In our study, the difference between limitations reported by patients with HFrEF and HFpEF disappeared when the regression model was adjusted by age, body mass index, and comorbidities.…”
Section: Perceived Limitations and Lvef Subtypementioning
confidence: 99%